0457 Development and utility of a mobile health application integrated with the electronic heath record for treatment of chronic insomnia disorder. (25th May 2022) - Morgenthaler, Timothy; Kolla, Bhanuprakash; Anderson, Sandra; Luedke, Tabitha; McColley, Samantha; Phillips, Sarah; Smith, Justin; Boudreau, Nancy; Harper, Sarah
Abstract: Introduction: Cognitive behavior therapy for insomnia (CBT-I), a first-line therapy for patients with chronic insomnia disorder (ChID), is underutilized due to reduced access to trained providers and other barriers. We developed an interactive care plan (ICP) combining individual aspects of CBT-I. This ICP, which integrates with the electronic health record (EHR), is designed to deliver personalized and scalable CBT-I to patients with ChID. We report data from initial implementation and evaluation of a ChID ICP deployed at a tertiary sleep medicine clinic. Methods: The ICP was developed following patient and provider interviews and focus groups. Patients diagnosed with ChID were offered enrollment and engaged in the ICP through an app. The ICP has embedded logic that may escalate care or offer an exit from the program, depending upon the patient's response to questions. Key variables ascertained from the patient included sleep efficiency (SE), sleep timing and the Insomnia Severity Index (ISI), and how satisfied they were with their progress (Likert scale). We also measured In Basket messaging related to use of the ICP. Results: A total of 222 patients [57% female, age=56.4±15.9 years (average ±SD), 92.7% white] were enrolled in the initial 120 days of ICP implementation. Most referrals were initiated by physicians or advanced practitioners (77.9%). ISI at initiation was 15±5.18 and SE was 74.55±16.65%. Patients spent 35.9±26.25 days engaging with the ICP. The ISI score at 28 days was 12.89±4.98 and SE was 78.9±13.4% with both showing significant improvement from baseline (p=0.013; p=0.002; respectively). Self-rated satisfaction with progress did not significantly correlate with actual improvement in ISI or SE (p>0.05). The ICP generated 3.89±2.3 In Basket messages per patient. Conclusion: Patients who actively engaged with the ICP showed significant improvements in insomnia severity and sleep efficiency. While a majority of the patients were neutral towards the ICP and only a small minority expressed dissatisfaction, these data indicate that the ICP will have clinical utility in busy sleep medicine practices with reduced access to behavioral sleep specialists. Support (If Any):